Optimalisasi Implementasi Basis Data NoSQL di AWS melalui Pemanfaatan AWS Skill Builder - Pangesti, Lintang Desy; Ardianto, Rian; Purwono, Purwono (Universitas Dharmawangsa, 2024)
Cloud computing has changed the paradigm of IT infrastructure by providing access to computing resources over the Internet, enabling organizations to manage their applications and data without having to manage the physical infrastructure. AWS (Amazon Web Services) is the leading choice in providing reliable and innovative cloud solutions, supporting a wide range of industries with scalable and secure services. However, in Indonesia, AWS implementation is still limited. The study investigates the use of AWS Skill Builder to implement NoSQL databases on AWS, highlighting the key role of case-based training and projects in accelerating the understanding and application of this technology. Through a systematic literature review approach, the study provides in-depth insight into how AWSSkill Builders can enhance user technical skills in managing and implementing NoSQL data bases effectively in an AWS environment.